Teacher Training Policies and Determination Of Inadequacies - CELEBI, Alper; OZRECBEROGLU, Nurdan; GUNES, Gunsel CAKIR; GEZERCAN, Yelda SERIN (Asian Journal of Contemporary Education, 2022)
Research conducted in this study aims to determine teachers’ opinions regarding how the primary school teacher training policies of the Turkish Republic of Northern Cyprus (TRNC) can be improved. For this purpose, 50 teachers working in primary education institutions were selected to determine the study group. Teachers’ opinions were collected through semi-structured interviews. Within the framework of the data obtained from the semi-structured interview forums, it has been tried to determine what are the points that are not considered sufficient in the primary school teacher training policies. Based on the results obtained, there were negative or unpopular opinions regarding teacher training, opinions about the training program adopted, opinions on teachers’ competence, opinions on which gains should be prioritized in teacher training programs, opinions about which courses and topics should be included in teacher training programs, and opinions on teacher training in general.